Maternal plasma metabolic fingerprint indicative for fetal Down syndrome. (5th September 2018) - Parfieniuk, Ewa; Samczuk, Paulina; Kowalczyk, Tomasz; Pietrowska, Karolina; Niemira, Magdalena; Paczkowska‐Abdulsalam, Magdalena; Wolczynski, Slawomir; Kretowski, Adam; Ciborowski, Michal; Zbucka‐Kretowska, Monika
Abstract: Objective: The objective of the study was to perform maternal plasma metabolic fingerprinting to evaluate differences in plasma metabolites between healthy and Down syndrome (DS) pregnancies and to indicate novel non‐invasive markers for DS prenatal diagnostics. Methods: This was a case‐control study of pregnancies between 15th and 18th gestational week. LC‐MS–based metabolic fingerprinting of plasma samples was performed. Results: Levels of five metabolites were significantly lower in the plasma of DS pregnancies. The majority of the statistically significant metabolites may be connected with fetal brain and central nervous system development (eg, fatty acid amides). According to the receiver operating characteristic (ROC), the combination of linoleamide and piperine has the highest diagnostic potential: area under the curve (AUC) = 0.878, sensitivity of 100%, and specificity of 73.3%. Conclusions: The study indicates disturbances in maternal metabolic pathways evoked by fetal DS. Novel potential maternal plasma metabolomic markers for non‐invasive prenatal diagnostics of fetal DS are proposed. Abstract : What is already known about the subject? Metabolomics has been applied in the search for differences between healthy and Down syndrome fetus using different matrices (maternal blood, urine, or amniotic fluid) and different techniques. What does this study add? Despite the fact that diagnosis is still based on invasive methodology, the present study indicates novel maternal metabolic pathways affected by fetal Down syndrome.